Development of Digital Books Based on the RANDAI Learning Model Integrated with West Sumatra Local Wisdom on Environmental Change Material - Nisrina Zakia Khalel; Fitri Arsih; Zulyusri Zulyusri; Rahmadhani Fitri (Jurnal Penelitian Pendidikan IPA, 2023)
Environmental damage can occur due to a person's lack of understanding about the environment, so the role of local wisdom needs to be revived to increase understanding regarding the environment. In understanding Environmental Change material, students need problem solving abilities. This problem-solving ability can be supported through problem-based learning models such as the RANDAI (Reciting, Analyzing, Narrating, Doing, Assesing & Implementing) learning model which is realized in the form of digital books. This type of research is development research using the Plomp model with preliminary research stages, prototyping phase, and assessment phase which are limited to practicality testing. The research subjects were three biology lecturers at Padang State University, two biology teachers and 26 students in class XI MIPA 3 at SMA Negeri 5 Pariaman. The instruments used were initial investigation questionnaires, self-evaluation questionnaires, expert review questionnaires, one to one evaluation questionnaires, small group evaluation questionnaires, field test questionnaires, and practicality questionnaires. Based on research conducted, the average validity value is 90.23% in the very valid category. The average practicality test by teachers and students is 88.21% in the practical category, so it can be concluded that the Digital Book Based on the Integrated RANDAI Learning Model of West Sumatra Local Wisdom on Environmental Change Material developed is very valid and practical